KAJIAN YURIDIS AGUNAN YANG DIAMBIL ALIH (AYDA) OLEH BANK - Putu Devi Yustisia Utami (Fakultas Hukum Universitas Dwijendra, 2019)
Banks in providing credit to community always prioritize the principle of prudence, however, any credit that has been provided by the bank has a risk. To minimize the risk of non performing loan by the debtor, banks often require collaterals. The collaterals submitted by the debtor is mostly in the form of land rights which is then be charged to the Encumbrance Right. When the debtor can’t pay the credit, the bank can execute the encumbrace right certificate of the collateral. However, in the fact that the execution of the encumbrance rights is not as easy as imagined, there are many obstacles that occur, so the bank tries to find other alternatives for the settlement of non performing loan with the Foreclosed Collateral (AYDA) process. In this study the author tries to examine the settlement of non performing loan by the Foreclosed Collateral (AYDA) process in terms of Law On Encumbrance Right. The conclusion in this study is, that the settlement of non performing loans through Foreclosed Collateral (AYDA) process as regulated in article 12 A of the Banking Law has violated the provisions of articles 12 and 20 of the Law On Encumbrance Right.This type of research is a normative legal research with a statutory approach and a legal concept analysis approach.Keywords : non performing loan, bank, collateral, AYDA